2014
DOI: 10.1073/pnas.1321871111
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen sulfide cytoprotective signaling is endothelial nitric oxide synthase-nitric oxide dependent

Abstract: Previous studies have demonstrated that hydrogen sulfide (H 2 S) protects against multiple cardiovascular disease states in a similar manner as nitric oxide (NO). H 2 S therapy also has been shown to augment NO bioavailability and signaling. The purpose of this study was to investigate the impact of H 2 S deficiency on endothelial NO synthase (eNOS) function, NO production, and ischemia/reperfusion (I/R) injury. We found that mice lacking the H 2 S-producing enzyme cystathionine γ-lyase (CSE) exhibit elevated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
323
1
14

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 327 publications
(346 citation statements)
references
References 50 publications
(64 reference statements)
8
323
1
14
Order By: Relevance
“…Our previous study indicated that H 2 S therapy increased nitrite levels and phosphorylation of eNOS Ser1177, resulting in cardioprotection in CSE KO mice and suggested significant cross‐talk between the H 2 S and NO signaling pathways 50. Therefore, we examined the hypothesis that nitrite therapy could also induce H 2 S production, contributing to the protection of cardiac function.…”
Section: Resultsmentioning
confidence: 98%
“…Our previous study indicated that H 2 S therapy increased nitrite levels and phosphorylation of eNOS Ser1177, resulting in cardioprotection in CSE KO mice and suggested significant cross‐talk between the H 2 S and NO signaling pathways 50. Therefore, we examined the hypothesis that nitrite therapy could also induce H 2 S production, contributing to the protection of cardiac function.…”
Section: Resultsmentioning
confidence: 98%
“…* P <0.05 relative to adult animals (100%). # P <0.05 relative to old rats, which were not treated with NaHS and homogenate of the heart from old rats should be separately noted, as the latter serves as a regulator of NO synthesis and powerful cardio-and vasoprotector [7][8][9][10]. The injection of exogenic hydrogen sulfide donor, NaHS, significantly increased the amount of H 2 S both in the mitochondria and homogenate of the heart from old animals, which was accompanied by a significant inhibition of both oxidative and nitrosative stress.…”
Section: Resultsmentioning
confidence: 99%
“…Nowadays, there has been increasing evidence for cNOS uncoupling as the primary source of O 2 • -in the cells [5,6]. On the other hand, it was shown that hydrogen sulfide (H 2 S) has positive cardiovascular effect through cNOS stimulation [7,8].That stimulation could be a result of cNOS recoupling. Thus H 2 S can lead to cNOS coupling and improve the functional state of the cardiovascular system with aging.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Особливої уваги потребує питання взаємодії H 2 S і NO. Згідно з останніми даними, H 2 S може збільшувати синтез NO як через фосфорилювання сNOS за PI3K/Akt-сигнальним механізмом, так і незалежно від нього [5,8]. Також відомо, що сірководень здатен пригнічувати фосфодіе-стеразу, фермент, що розщеплює цГМФ у клітині, і пролонгувати цим самим дію NO на ГМ [9][10][11].…”
Section: вступunclassified